Qualified audit opinions and stock prices - Dodd, Peter; Dopuch, Nicholas; Holthausen, Robert; Leftwich, Richard (Journal of Accounting and Economics, 1984)
We investigate whether announcements of ‘subject to’ audit opinions and disclaimers of opinions affect stock prices. The results indicate that many firms experience negative abnormal performance prior to the release of qualified opinions, and that the magnitude of prior abnormal performance differs across types of qualifications. However, there is little evidence of a stock price effect when qualifications are disclosed publicly. It is difficult to construct powerful tests of the announcement effect of a qualified opinion for three reasons. First, the announcement date of the qualification is not easily identified. Second, measuring the unanticipated component of the announcement requires a model of market expectations. Third, controls must be employed for concurrent disclosures. The problems concerning event date identification have ramifications for other accounting event studies, particularly studies of disclosures typically contained in the annual report or 10-K.